Effect of quilting suture interval on donor site seroma after latissimus dorsi muscle flap - Ghumman, Ammad Rasul; Raza, Dr Muhammad Sheraz (Journal of Ayub Medical College Abbottabad, 2021)
debilitating complication. Many methods were implemented but quilting sutures remains the excellent option to counter this issue. But distance between quilting sutures still remain under debate, so to address this issue current study was devised to analyse and gather date regarding post-operative seroma rates at different intervals of quilting sutures. Methods: This study was done in Jinnah burn and reconstructive centre, Lahore from January 2016 to September 2017.In accordance to quilting distance, all patients were assigned randomly into three groups: 6-cm quilting (n=12), and 3-cm quilting (n=12), non- quilting (n=10). Primary outcome measures were the drainage volume, removal time, seroma formation, frequency of aspiration and recovery time. Results: No significant difference were found in quilting group. Drain removal time is shorter in the 6-cm quilting and 3-cm quilting groups as compared to non-quilting as well as drain output which was significantly decreased in quilting group. The rate of seroma formation and frequency of aspiration was much higher in non-quilting group as compared to 6-cm quilting and 3-cm quilting groups. Conclusion: Quilting is a reliable way in prevention of seroma formation and reducing its volume. Our findings indicate the 6-cm suture interval is enough to avoid these complications. Keywords: Seroma; Latissimus dorsi flap; Quilting sutures